Understanding factors influencing HPV vaccine uptake among caregivers in Kwara State, Nigeria: A qualitative study - Abdulmujeeb Opeyemi Muhammad-Olodo; Laura Asher (PLoS ONE, 2026)
Introduction Human papillomavirus (HPV) vaccine prevents over 90% of cervical cancers. In October 2023, Nigeria launched a free HPV vaccination campaign targeting girls aged 9–14 years. Despite removing cost barriers, misinformation about fertility impacts and population control contributed to variable uptake across states. Understanding caregiver decision-making is crucial for improving coverage. This study aimed to explore factors influencing caregivers’ HPV vaccination decisions during Nigeria’s 2023 campaign in Ilorin East Local Government Area, Kwara State. Methods A qualitative study using focus group discussions (FGDs) was conducted using purposive and snowball sampling. We recruited 41 caregivers (mean age 47 years; 71% female) of eligible girls from urban and rural communities. Five FGDs were conducted: four with vaccine acceptors (n = 35) and one with decliners (n = 6). Discussions were conducted in Yoruba, audio-recorded, transcribed verbatim, and analysed using Braun and Clarke’s reflexive thematic analysis. Ethical approval was obtained from two institutional review boards. Results Four themes emerged from the analysis. Trust operated at multiple levels: institutional (government programmes), interpersonal (healthcare worker competence), and community (religious/traditional leader endorsement). Historical medical mistrust, intensified by COVID-19 experiences, may have manifested as fertility and population control fears. Personal cancer experiences strongly motivated acceptance, whilst concerns about childhood sexuality influenced timing preferences. Despite free provision, barriers included geographic inequities (remote Fulani-Hausa communities were excluded), language barriers (no Hausa translators), school-based delivery gaps, and indirect costs (transport, time). Caregivers recommended house-to-house campaigns, multilingual services, traditional leader engagement, and permanent vaccination centres. Conclusion Free vaccine provision is necessary but not sufficient to ensure uptake. Successful HPV vaccination requires rebuilding trust through community engagement, addressing historical medical exploitation concerns, and ensuring equitable access. Integrating these findings into Nigeria’s National Programme on Immunisation could improve coverage from current estimates of 54% to targeted 90%, protecting more girls from cervical cancer whilst respecting community values.